Kualitas Proses Bimbingan Skripsi Mahasiswa Jurusan Tadris Biologi IAIN Kerinci di Masa Pandemi Covid 19 - Juita, Dewi; M, Yusmaridi (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
This research was conducted with the aim of obtaining a description of the quality of the minithesis guidance process that took place during the covid-pandemic period in Biology Education Department IAIN Kerinci and student satisfaction in carrying out the guidance process during the pandemic. The research method used is a descriptive method with a questionnaire instrument quality process guidance minithesis and written interviews online. Data were analyzed using descriptive statistics. The results obtained by the quality of the minithesis guidance process of students during the pandemic are in the good category with an average of 66.4. Media that are widely used during the minithesis guidance process are whatsApp and email. As many as 60% of the sample of students were satisfied with the guidance process they went through during the pandemic. The minithesis guidance process experiences many obstacles, one of which is in terms of guidance time and ineffective communication between the supervisor and students. The solutions provided by students include continuing to carry out offline counseling by paying attention to health protocols.